KEADILAN DALAM PERSPEKTIF AGAMA DAN FILSAFAT MORAL - Moh Fachri (Prodi Hukum Keluarga Fakultas Agama Islam Universitas Nurul Jadid, 2018)
Justice is essentially an ethical concept, a moral concept. As a moral concept, justice aims to seek improvement for everyone. To work for the good for everyone, the interests of each person need to be cared for without giving birth to gold or bringing someone else's eyes. Justice has meaning as the fulfillment of the rights of every person to be respected and cared for by each of the same degrees, both in preserving, advancing and enjoying their lives.Justice, not just a value that only exists, and is owned by someone. But, it must be realized in real life in relation to others. The religion which contains the teachings of the truth of the highest and absolute values teaches its adherents to do justice, act fairly, be fair, and act fairly in making decisions, and in all areas of their lives. In fact, injustice still happens everywhere. This happened, because none of the reasoning was functioning properly, and the bluntness of one's conscience which included the cause of the injustice.Keyword: Justice, Religion, Moral Philosophy